Glycogen Storage Disease: An Unusual Presentation - Afroza, Syeda; Rouf, MA; Haque, MM (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Glycogen storage disease(GSD) are a group of disorders caused by lack of enzymes involved in glycogen synthesis or breakdown with buildup of glycogen in tissue. The incidence of glycogen storage disease (GSD) is not uncommon in paediatric population. We report the case of a twelve year old boy of glycogen storage disease who presented with gradual abdominal distension since his two years of age and two episodes of epistaxis. There was no history of jaundice, blood transfusion, convulsion, contact with TB patient, travelling to malaria or kala azar endemic zone or deterioration of school performance. On examination, he was mildly pale, stunted and had gross hepatosplenomegaly. The single positive lab investigation in this case was increased triglyceride and the final diagnosis was made by liver biopsy. After diagnosis, treatment was provided by counseling and appropriate feeding advice. This case is being reported because this type of presentation with gross hepatosplenomegaly without a single episode of convulsion is unusual in glycogen storage disease, and the age of presentation is also late. J Bangladesh Coll Phys Surg 2015; 33(1): 48-51